2001
DOI: 10.1038/sj.jea.7500159
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprinting PCB patterns among Mohawk women

Abstract: This study examined the association of contaminated fish consumption and polychlorinated biphenyl ( PCB ) body burden by comparing the similarity of the congener pattern in yellow perch, caught near the point source of industrial pollution, and in other local fish to the pattern found in the breast milk of Mohawk women from Akwesasne, a Native American community located along the St. Lawrence River in New York, Ontario, and Quebec. The similarity is defined by the weighted Euclidean distance between two congen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…Similarly, men with jobs that were evaluated by industrial hygienists as entailing exposure to PCBs were significantly more likely than men without occupational exposure to have a serum congener pattern that resembled Aroclor 1248, the commercial PCB mixture used at all three local facilities. The association between local fish consumption and serum congener pattern among Mohawk men is consistent with our earlier work that showed nursing Mohawk women who ate the local fish most also showed congener patterns in their breast milk that more closely resembled the pattern in contaminated local fish (Hwang et al, 2001). These findings strengthen the argument that local exposures to PCBs through fish consumption or occupation have resulted in exposure to PCBs among the Mohawk people.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Similarly, men with jobs that were evaluated by industrial hygienists as entailing exposure to PCBs were significantly more likely than men without occupational exposure to have a serum congener pattern that resembled Aroclor 1248, the commercial PCB mixture used at all three local facilities. The association between local fish consumption and serum congener pattern among Mohawk men is consistent with our earlier work that showed nursing Mohawk women who ate the local fish most also showed congener patterns in their breast milk that more closely resembled the pattern in contaminated local fish (Hwang et al, 2001). These findings strengthen the argument that local exposures to PCBs through fish consumption or occupation have resulted in exposure to PCBs among the Mohawk people.…”
Section: Discussionsupporting
confidence: 81%
“…However, in our previous work, we weighted the Euclidean distances for each congener by a factor representing its relative half-life, and the results were similar to those without such weighting (Hwang et al, 2001). Another limitation of the study pertains to the accuracy of the self-reported information regarding lifetime fish consumption.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations